Aspectos lexicais da Língua Brasileira de Sinais: glossário em libras da região metropolitana do Cariri do Ceará - Santos, Adriano Rodrigues dos (2021)
On this dissertation we developed a bilingual Libras glossary, of the Metropolitan area of Cariri on Ceará, with the terminology of Cariri´s tourist sites. This glossary of Cariri´s tourist sites is of extreme importance to document and to register the naturally expressed signs of the deaf community of the region, as well as to aid the people who are part of said to community to learn these specific signs. We also aim to enrich the lexicon of Libras. In order to get acquainted with the lexicon, so as to organise the Glossário em Libras da Região Metropolitana do Cariri do Ceará, with special focus on the lexicon used by the deaf of the cities of Juazeiro do Norte e Crato, particularly the the terms related to the tourist sites, we took as our starting point, both the contents and the words related to them, taken out of a website called “turismo no Cariri”, through the link https://www.turismonocariri.com.br. The universe of this research is mainly the study of the natural language of the deaf on the deaf community of the metropolitan area of Cariri on Ceará, focusing both on the lexicon of the signs, as well as on the ways in which the deaf perform these signs. Thus, this research has contributed to ensure and to value the signs used by the deaf on this area, as well as, specially, their language, their stories and cultures in the society we live in, mainly made out of the hearing. Upon what has been studied and researched so far, this paper contributes to the area of LIBRAS, concerning the register, organisation and creation of entries in bilingual terminographic works, it also contributes by encouraging future new researches on the development of new terminological repertoire in Libras. We researched here the signs for 70 words in Portuguese. Analysing all of the videos, we found 56 signs expressed by the deaf participants.